2000
DOI: 10.1084/jem.192.7.965
|View full text |Cite
|
Sign up to set email alerts
|

Cd1b-Mediated T Cell Recognition of a Glycolipid Antigen Generated from Mycobacterial Lipid and Host Carbohydrate during Infection

Abstract: T cells recognize microbial glycolipids presented by CD1 proteins, but there is no information regarding the generation of natural glycolipid antigens within infected tissues. Therefore, we determined the molecular basis of CD1b-restricted T cell recognition of mycobacterial glycosylated mycolates, including those produced during tissue infection in vivo. Transfection of the T cell receptor (TCR) α and β chains from a glucose monomycolate (GMM)-specific T cell line reconstituted GMM recognition in TCR-deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
107
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 139 publications
(109 citation statements)
references
References 49 publications
2
107
0
Order By: Relevance
“…T-cell recognition is highly specific for the precise structure of natural GMM including the glucose, the linkage of the glucose to the mycolate and the R,Rstereochemistry of the hydroxyl acid part of the mycolate [57]. Upon infection mycobacteria begin to produce GMM which provides a good indicator of local invasion.…”
Section: Other Mycolate Estersmentioning
confidence: 99%
“…T-cell recognition is highly specific for the precise structure of natural GMM including the glucose, the linkage of the glucose to the mycolate and the R,Rstereochemistry of the hydroxyl acid part of the mycolate [57]. Upon infection mycobacteria begin to produce GMM which provides a good indicator of local invasion.…”
Section: Other Mycolate Estersmentioning
confidence: 99%
“…The possible role of MHC class Ib-restricted CD8 ϩ T cells during chronic bacterial infection, such as tuberculosis, is not known. In recently infected humans, Lewinsohn et al (20,21) showed that the vast majority of Mtb-reactive, CD8 ϩ T cells in the peripheral blood are restricted by the MHC class Ib molecule, HLA-E. CD1-restricted CD8 ϩ T cells have also been isolated from peripheral blood of infected individuals (22)(23)(24). In mice, Mtbreactive CD8 ϩ T cells restricted by the MHC class Ib molecule, H2-M3, have been identified (25) (26).…”
Section: Cd8 ϩ T Cells Also Infiltrate the Lung Following Infection Withmentioning
confidence: 99%
“…Human monocytes were isolated from peripheral blood using Ficoll and adherence to tissue-culture flasks and were cultured in RPMI 1640 medium with 10% FBS (33). In selected experiments, monocytes were further depleted of residual lymphocytes using anti-CD20 (L26), anti-CD3 (TCS3), anti-CD56 (B159), and goat anti-mouse Ig-coated magnetic beads (Dynal) such that lymphocytes constituted Ͻ2% of total cells as determined by flow cytometric staining with non-cross-reactive lymphocyte markers.…”
Section: Cells and Flow Cytometrymentioning
confidence: 99%